2014
DOI: 10.5152/imj.2014.24993
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Neurological Disabilities by the Disability Scale Published on 16.12.2010

Abstract: Özürlülüğün tanımı ve özürlülere sağlık kurulu raporlarının nasıl verilmesi gerektiği ile ilgili mevzuat, Bakanlar Kurulu'nun 16.12.2010 tarih ve 27787 sayılı resmi gazetede yayımlanan "Özürlülük ölçütü, sınıflandırması ve özürlülere verilecek sağlık kurulu raporları hakkında yönetmelik" ile düzenlenmiştir. Özürlü; doğuştan veya sonradan, bedensel, zihinsel, ruhsal, duygusal ve sosyal yeteneklerini çeşitli derecelerde kaybetmesi nedeniyle toplumsal yaşama uyum sağlama ve günlük gereksinimlerini karşılamada güç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Several studies from Turkey that have evaluated the neurological causes of disability, as determined by a health board in a tertiary center, have reported that stroke and dementia were two of the most common neurological diseases, consistent with the findings of our study (6,21,22). The patient populations of these studies were younger than that of our study's, and included all severity levels.…”
Section: Neurological Diseasessupporting
confidence: 91%
“…Several studies from Turkey that have evaluated the neurological causes of disability, as determined by a health board in a tertiary center, have reported that stroke and dementia were two of the most common neurological diseases, consistent with the findings of our study (6,21,22). The patient populations of these studies were younger than that of our study's, and included all severity levels.…”
Section: Neurological Diseasessupporting
confidence: 91%